1998
DOI: 10.1093/oxfordjournals.aje.a009388
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Pets as Risk Factors for Alveolar Hydatid Disease in Austria

Abstract: To identify the risk of pet ownership (i.e., cats and dogs) for alveolar echinococcosis caused by Echinococcus multilocularis, the habits and activities of 21 patients (histologic confirmation or positive serology with corresponding evidence on an ultrasonogram, radiograph, or computed tomography scan) in Austria during the period 1967-1997 were compared with the habits and activities of 84 controls matched by sex, age, and residence. Cat ownership (odds ratio (OR) = 6.47, 95% confidence interval (CI) 1.54-27.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
4
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 6 publications
1
55
4
5
Order By: Relevance
“…5,31 Recently, a case-control study with 21 AE patients from Austria identified cat ownership and hunting in forests as independent risk factors, while agricultural activity was not identified as high-risk. 4 In our study, none of the factors mentioned was found to be significantly correlated with seroreactors or cases. It has to be noted, however, that the retrospective studies mentioned were based on confirmed AE cases, while in our study the risk was largely evaluated with seroreactors.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…5,31 Recently, a case-control study with 21 AE patients from Austria identified cat ownership and hunting in forests as independent risk factors, while agricultural activity was not identified as high-risk. 4 In our study, none of the factors mentioned was found to be significantly correlated with seroreactors or cases. It has to be noted, however, that the retrospective studies mentioned were based on confirmed AE cases, while in our study the risk was largely evaluated with seroreactors.…”
Section: Discussioncontrasting
confidence: 62%
“…Contaminated foodstuffs from the environment eaten uncooked and infected dogs and cats carrying the tapeworm eggs in their fur are suspected to be important sources of infection. 4 In parts of Europe, AE seems to be an occupational hazard for farmers, 5,6 who may be at risk by handling contaminated soil or by inhaling dust containing eggs during farming activities. The primary location of the parasite in humans is the liver, although metastases may form elsewhere in later stages of the disease.…”
mentioning
confidence: 99%
“…In the Alaskan study, 7 the risk of disease was associated with dog ownership and residence in a dwelling constructed directly over the tundra. The Austrian study found no association between dog ownership and a higher risk of disease, 8 possibly because dogs enjoy greater freedom of movement in Alaska than they do in Austria and the likelihood of Austrian dogs ingesting carrion is therefore lower. Nevertheless, cat ownership was significantly associated with E. multilocularis infection, a variable not considered in the Alaskan study.…”
Section: Discussionmentioning
confidence: 94%
“…7,8 These studies analyzed 19 and 23 cases of alveolar echinococcosis caused by the larval phase of E. multilocularis that occurred in Alaska and Austria, respectively. In the Alaskan study, 7 the risk of disease was associated with dog ownership and residence in a dwelling constructed directly over the tundra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation